PERAN AGENDA BUILDING BAGI PUBLIC RELATIONS - Farikha Rachmawati (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
Public relations performs issue management as an effort to maintain the image and reputation of the agency. This study aims to determine the role of public relations in making agendas that increase the positive image of the government. This research is academically useful in developing a distinctive theory of public relations, namely the agenda of building information subsidies. The results show that public relations applies an agenda building strategy in narrative production. The theory of agenda building & information subsidies is used by public relations for positive public perception of the government. Agenda building starts from the planning process carried out by the crisis team, coordination meetings to sharpen issues, making communication strategies, media monitoring, media relations, news tone analysis, narrative production, evaluation, and information subsidies. Public relations has implemented the concept of agenda building information subsidies to influence public opinion through issue management with several steps, namely highlighting certain issues, paying attention to issues, framing media, connecting issues with other symbols, utilizing big data and artificial intelligence to capture issues comprehensively. Qualitative research was conducted by conducting interviews with 10 public relations workers working in government agencies. public relations utilizes various media to maximize agenda building, such as: big data, press conferences, websites, releases, twitter, Instagram, facebook, youtube live streaming, and so on. Data analysis using miles, hubberman, saldana and validity test with source triangulation.